Hollow Justice - DAVID E. WILKINS (Yale University Press, 2013)
In the fall of 1980 I arrived in Tucson, Arizona, excited to be embarking on a master’s degree in federal Indian policy, under the auspices of the Political Science Department at the University of Arizona. The program, the first of its kind in the nation, had been developed by that singular indigenous figure Vine Deloria, Jr. I quickly discovered that Deloria and his political science colleagues had designed a curriculum that was equal parts politics, policy, law, and history. In each class he taught, Deloria emphasized that students needed a deep, unvarnished, and unrelenting immersion in each of these broad and interrelated areas in order to understand the contemporary status of indigenous nations. He stressed that a new kind of academic was being groomed by this unique program: the policy specialist. This person, after taking a bevy of seminars and regular courses offered by Deloria, Clifford M. Lytle, Thomas Holm, Robert K. Thomas, and others—including, for example, Development of Federal Indian Policy (a two-part course spread over two semesters), Congress and the American Indian, American Indians and the Supreme Court, Tribal Government, Indian Water Rights, Indian Treaties—would be capable of conducting research, analyzing data, and preparing reports or testimony on Native land disputes, boundary problems, hunting and fishing rights cases, treaty rights, intergovernmental conflicts and would be effective in the classroom as well. Deloria had several degrees, including a law degree. Early in his career he opted not to become a full-time lawyer. Instead, he liberally critiqued the discipline’s practitioners and doctrines and wrote searching reviews of leading casebooks, while teaching a number of law-related courses at several of the universities with which he was affiliated over the years. Well aware of the powerful position of law in American society, and in the way it has been used to contour the status of Native nations, their citizens, and indigenous relations with the federal and state governments, Deloria teamed up with Clifford Lytle, a constitutional law expert in the Political Science Department at Arizona in the early 1980s; together they wrote two major and well-received books.